Optimizing Nursing Workload Through EMR-Based Documentation: A Case Study at Welas Asih Regional Hospital - Luzi Anjani Hasanah; Meilati Suryani; Hartati (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
The development of information technology in the era of the Industrial Revolution 4.0 has encouraged hospitals to implement Electronic Medical Records (EMR) as part of the Hospital Management Information System (SIMRS). EMR implementation is expected to improve patient safety, documentation quality, and nursing efficiency. However, the use of EMR may also affect nurses’ workload, particularly in inpatient settings where documentation demands are high.  This study aimed to determine the relationship between the implementation of nursing care documentation using the EMR application and nurses’ workload in the medical-surgical inpatient unit of Welas Asih Regional Hospital. This study used a cross-sectional design with a total sampling technique involving 35 nurses working in the medical-surgical inpatient unit. Data were collected using a modified questionnaire that had been tested for validity. The results showed that most nurses implemented nursing care using EMR well (54.3%), and the majority experienced a moderate workload (40.0%). Bivariate analysis revealed a significant relationship between EMR implementation and nurse workload (ρ-value = 0.026; α < 0.05), indicating that better EMR implementation was associated with lighter nurse workload. There is a significant relationship between the implementation of nursing care documentation using the EMR application and nurses’ workload in the medical-surgical inpatient unit. Effective EMR implementation can help reduce nurse workload and support better nursing care delivery. Continuous system improvement, adequate infrastructure, and ongoing training are necessary to optimize EMR use in clinical practice.